Moisture sorption characteristics of freeze dried whey–grape beverage mix - Varghese, K. Shiby (Springer India, 2012)
Moisture sorption isotherms of freeze dried whey–grape beverage powder were determined at 20, 30 and 40 °C. A gravimetric static method was used under 0.11–0.85 water activity range and the sorption isotherms were found to be Type II. Various mathematical models were fitted to experimental data and it was found that Peleg model suits best in describing the equilibrium moisture content–equilibrium relative humidity relationships of instant whey–grape beverage mix over the range of temperatures studied. The net isosteric heat of sorption varied between 5.22 and 1.12 KJ/mol at moisture level varying between 1 and 9 % db. At moisture content below 1 % (db) the isosteric heat of sorption increased sharply for freeze dried whey–grape beverage powder and value of 49.08 KJ/mol was estimated.